Influence of deformation process on microstructure and properties of 2014 aluminium alloy. Issue 13 (1st September 2020) - Li, Fushan; Chen, Songyi; Chen, Kanghua; Huang, Lanping; He, Longlong; Chen, Geng
Abstract : The comparisons of forging-extrusion multistage hot deformation, forging and extrusion hot deformation processes on microstructure, mechanical property and impact toughness of 2014 Al alloy have been investigated. Results showed that the strength and impact toughness of the samples under forging-low extrusion multistage deformation process were significantly improved compared with that under forging deformation process due to the formation of smaller insoluble particles, finer grains and higher density of matrix precipitates. However, the strength and impact toughness of the samples under forging-extrusion multistage hot deformation process are lower than that under extrusion hot deformation process. The strengthening and fracture mechanisms with different deformation process have been discussed in detailed.